TRAINING OF COOPERATION AND AGRICULTURAL MUTUALITY OFFICERS IN FRENCH WEST AFRICA (1955-1958) - SEKA, Jean-Baptiste; KONAN, Koffi; KOFFI, Alexis (IJRDO - Journal of Social Science and Humanities Research, 2022)
In the perspective of a rational exploitation of French West Africa colonies (FWA), the colonial administration considered to put right the "loss of balance" between the rural and urban world. To this end, it proceeded to training and integrating players responsible for promoting and developing the rural world: the cooperation and agricultural mutuality officers. This article therefore aims to present the training outlines and socio-professional integration of the cooperation and agricultural mutuality officers. To achieve this objective, archive folders of Q series (economic affair), the 5Q sub-series of the Senegal national archives, were exploited. The data in this series were criticized and cross-checked with scientific publications. Based on such a methodological approach, the research reveals, on the one hand, the motivations for training and, on the other hand, the recruitment of cooperation and agricultural mutuality officers. These are linked to the need to have senior African executives capable of supervising farmers and, by extension, to guide the cooperative structures with an agricultural vocation. Also, the training sessions organized in modules are tuned over time to consider the realities on the ground and needs. The reorientation of curricula and specialization of the training centers are made to consider agro-climatic conditions and cultural specificities of the agricultural regions.